Dynamic transcriptomic responses to soybean cyst nematode infection in soybean genotypes with contrasting resistance profiles - Nissan, Nour; Puchacz, Nathalie; Hooker, Julia C.; Ste-Croix, Dave T.; Zapata, Gerardo; Lefebvre, François; Charette, Martin; Golshani, Ashkan; Cober, Elroy; Mimee, Benjamin; Samanfar, Bahram (Frontiers in Plant Science, 2025)
IntroductionSoybean cyst nematode populations are rapidly evolving to overcome the limited genetic resistance currently employed in commercial soybean varieties, threatening the future of crop production. To mitigate that, it is crucial to identify novel sources of resistance. Soybean lines PI 561310 and PI 567295 were previously found to exhibit partial SCN resistance despite lacking resistant alleles at rhg1 and Rhg4. MethodsIn an attempt to elucidate their resistance mechanisms, PI 561310 and PI 567295 alongside susceptible Essex and resistant Peking and PI 88788 lines were infected with SCN HG type 0. Control and infected root tissues were collected at 5 and 10 day post-infection for RNA sequencing and comparative transcriptomic response analyses were performed.Results and discussionThe resistance mechanism employed by PI 561310 appears to be driven by the expression of PAL, which positively regulates downstream lignin, flavonoid and salicylic acid biosynthesis pathways. PI 567295 displayed a unique and divergent transcriptomic response characterized predominantly by gene downregulation, rather than the canonical upregulation observed during defense activation; an atypical response suggestive that PI 567295 employs a distinct mechanism not previously described in the literature. This study explores the diversity of defense strategies and provides valuable insight into novel genetic origins of SCN resistance as we navigate the landscape of evolving SCN parasitism.